Snakebite Envenomation in Benue State: A Study of Prevalence and Treatment Approach in Otukpo Local Government Area, Benue State, Nigeria - G. Ada; R. Malik; B. A. Onuh; Y. O. Peter; S. Dahiru; N. D. Baba; M. A. Titilayo; G. Bilbonga; E. D. Abel (Journal of Applied Sciences and Environmental Management)
Snakebite envenomation occurs frequently in the studied area, but the prevalence and management approach has not been verified. Therefore, the study aimed to assess the prevalence, and management of snakebite covering a period of ten years (January 2011 to December 2020). One hundred and fifty (150) questionnaires were administered to respondents and analysed using descriptive statistics. The result indicated 131(87.3%), of the snakebite victims, were males, while 19 (12.7%) were female. The incidence was highest among 30-39 years, while the least was among 60-69 years and above. In addition, farmers had the highest percentage of snakebite 140(93.3), followed by traders 6(4.0%), with the least being civil servants and other occupational 2(1.3%). More so, about 80(53.3%) of the victims had secondary education, followed by 54(36.0%) primary education, while 6(4.0%) of them obtained tertiary education and non-formal education 10(6.7%) respectively. Dendroaspis viridis 36(24%) with the highest number of victims, followed by Echis ocellatus 34(22.7%), Bitis ariatas,32(21.3), Naja negricollis 16(10.7%), Atractaspis species 4(2.7%), and unidentified species 28 (18.7%) respectively. Most of the snakebites occurred during the dry season with 87(58%), while 63(42%) occurred in the rainy season. About 145(96.7%) victims south for herbalists, while only 2(1.3%) for orthodox medicine and others.  This result signified that victims strongly believe in the traditional way of snakebite treatment rather than orthodox medicine.